Generation of Powerful Human Tolerogenic Dendritic Cells by Lentiviral-Mediated IL-10 Gene Transfer - Comi, Michela; Amodio, Giada; Passeri, Laura; Fortunato, Marta; Santoni de Sio, Francesca Romana; Andolfi, Grazia; Kajaste-Rudnitski, Anna; Russo, Fabio; Cesana, Luca; Gregori, Silvia (Frontiers in Immunology, 2020)
The prominent role of dendritic cells (DC) in promoting tolerance and the development of methods to generate clinical grade products allowed the clinical application of tolerogenic DC (tolDC)-based therapies for controlling unwanted immune responses. We established an efficient method to generate tolerogenic human DC, producing supra-physiological levels of IL-10, by genetically engineering monocyte-derived DC with a bidirectional Lentiviral Vector (bdLV) encoding for IL-10 and a marker gene. DCIL-10 are mature DC, modulate T cell responses, promote T regulatory cells, and are phenotypically and functionally stable upon stimulation. Adoptive transfer of human DCIL-10 in a humanized mouse model dampens allogeneic T cell recall responses, while murine DCIL-10 delays acute graft-versus-host disease in mice. Our report outlines an efficient method to transduce human myeloid cells with large-size LV and shows that stable over-expression of IL-10 generates an effective cell product for future clinical applications in the contest of allogeneic transplantation.